2021
DOI: 10.3390/polym13213629
|View full text |Cite
|
Sign up to set email alerts
|

Validating Poly(3,4-ethylene dioxythiophene) Polystyrene Sulfonate-Based Textile Electroencephalography Electrodes by a Textile-Based Head Phantom

Abstract: It is important to go through a validation process when developing new electroencephalography (EEG) electrodes, but it is impossible to keep the human mind constant, making the process difficult. It is also very difficult to identify noise and signals as the input signal is unknown. In this work, we have validated textile-based EEG electrodes constructed from a poly(3,4-ethylene dioxythiophene) polystyrene sulfonate:/polydimethylsiloxane coated cotton fabric using a textile-based head phantom. The performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…2457.759. An OpenBCI Board with a built-in ADS1299 [9] for impedance testing was also used to assess skin-to-electrode impedance according to Tseghai et al [10], shown in Figure 1c. Besides, a textile head phantom was used to determine the signal-to-noise ratio (SNR) of the textrode according to Tseghai et al [11], shown in Figure 1d.…”
Section: Methodsmentioning
confidence: 99%
“…2457.759. An OpenBCI Board with a built-in ADS1299 [9] for impedance testing was also used to assess skin-to-electrode impedance according to Tseghai et al [10], shown in Figure 1c. Besides, a textile head phantom was used to determine the signal-to-noise ratio (SNR) of the textrode according to Tseghai et al [11], shown in Figure 1d.…”
Section: Methodsmentioning
confidence: 99%
“… Types of EEG electrodes: ( a ) gold cup EEG electrode [ 11 ], under CC by 4.0; ( b ) capacitive EEG electrode [ 17 ], under CC by 4.0; ( c ) dry EEG comb electrode [ 28 ], under CC by 4.0; ( d ) dry EEG flat electrode [ 29 ], under CC by 4.0. …”
Section: Figurementioning
confidence: 99%
“…13,14 For example, EEG is used to diagnose epilepsy, sleep disorders, and attention-deficit hyperactivity disorder. 15 There are five common types of brain biosignal frequency ranges in the medical sector, denoted by the Greek alphabet: delta (0.5-3 Hz), theta (4-7 Hz), alpha (8-13 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (30-100 Hz). 16 Postsynaptic potential is responsible for brain electroactivity.…”
Section: Basics Of Eeg and Current Measurement Devicesmentioning
confidence: 99%
“…15 There are five common types of brain biosignal frequency ranges in the medical sector, denoted by the Greek alphabet: delta (0.5-3 Hz), theta (4-7 Hz), alpha (8-13 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (30-100 Hz). 16 Postsynaptic potential is responsible for brain electroactivity. An electric dipole is created due to the current flow in the brain.…”
Section: Basics Of Eeg and Current Measurement Devicesmentioning
confidence: 99%